MEMBANGKITKAN MINAT BELAJAR MATEMATIKA DENGAN MEDIA PEMBELAJARAN INTERATIF - EDY SUWANTO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Mathematics learning during the Covid-19 pandemic at SMA Negeri 1 Karangrayung did not run optimally, many students did not take online learning, did not do assignments, and there were even some students who did not take daily assessments. This indicates that the interest in learning mathematics in students is in the low category. To overcome these problems, it is necessary to use learning media that can arouse students' interest in learning. One solution is to use interactive learning media. The purpose of this study was to determine interest in learning mathematics during the Covid-19 pandemic, to find out the positive impact of using interactive learning media in learning mathematics, and to generate interest in learning mathematics with interactive learning media in class XII MIPA students at SMA Negeri 1 Karangrayung. The place of this research is SMA Negeri 1 Karangrayung, Grobogan Regency. The subjects in this study were all students of class XII MIPA in the academic year 2021/2022, with a total of 139 students consisting of 46 males and 93 females. The method in this study is to compare the data on interest in learning mathematics in the initial conditions with data on interest in learning mathematics in the final conditions. Data on interest in learning mathematics in the initial conditions were obtained from questionnaires given before students used interactive learning media in learning mathematics. While the data on interest in learning mathematics in the final condition was obtained from a questionnaire given after students used interactive learning media in learning mathematics. The results of this study indicate that the percentage of interest in learning mathematics for the high category in the initial condition is 40.29%, and in the final condition it is 82.01%. While the percentage of interest in learning mathematics for the low category in the initial condition was 59.71% and in the final condition it was 17.99%. These results prove that the use of interactive learning media can generate interest in learning mathematics in class XII MIPA students at SMA Negeri 1 Karangrayung in 2021. ABSTRAKPembelajaran matematika pada saat pandemi Covid-19 di SMA Negeri 1 Karangrayung tidak berjalan dengan maksimal, banyak peserta didik yang tidak mengikuti pembelajaran daring, tidak mengerjakan tugas, dan bahkan ada beberapa peserta didik yang tidak mengikuti penilaian harian. Hal tersebut mengindikasikan bahwa minat belajar matematika pada peserta didik dalam kategori rendah. Untuk mengatasi permasalahan tersebut maka perlu media pembelajaran yang dapat membangkitkan minat belajar peserta didik. Salah satu solusinya yaitu dengan menggunakan media pembelajaran interaktif. Tujuan penelitian ini untuk mengetahui minat belajar matematika di saat pandemi Covid-19, mengetahui dampak positif dari penggunaan media pembelajaran interaktif dalam pembelajaran matematika, dan membangkitkan minat belajar matematika dengan media pembelajaran interaktif pada peserta didik kelas XII MIPA di SMA Negeri 1 Karangrayung. Tempat penelitian ini di SMA Negeri 1 Karangrayung, Kabupaten Grobogan. Subjek dalam penelitian ini adalah semua peserta didik kelas XII MIPA pada tahun pelajaran 2021/2022, dengan jumlah 139 peserta didik yang terdiri 46 laki-laki dan 93 perempuan. Metode dalam penelitian ini dengan membandingkan antara data minat belajar matematika pada kondisi awal dengan data minat belajar matematika pada kondisi akhir. Data minat belajar matematika pada kondisi awal diperoleh dari kuisioner yang diberikan sebelum peserta didik menggunakan media pembelajaran interaktif dalam belajar matematika. Sedangkan data minat belajar matematika pada kondisi akhir diperoleh dari kuisioner yang diberikan setelah peserta didik menggunakan media pembelajaran interaktif dalam belajar matematika. Hasil dari penelitian ini menunjukkan bahwa persentase minat belajar matematika untuk kategori tinggi pada kondisi awal sebesar 40,29%, dan pada kondisi akhir menjadi 82,01%. Sedangkan persentase minat belajar matematika untuk kategori rendah pada kondisi awal sebesar 59,71% dan pada kondisi akhir menjadi 17,99%. Hasil tersebut membuktikan bahwa penggunaan media pembelajaran interaktif dapat membangkitkan minat belajar matematika pada peserta didik kelas XII MIPA di SMA Negeri 1 Karangrayung tahun 2021.